VARIASI LAMA WAKTU PERENDAMAN KULIT PISANG TANDUK DALAM LARUTAN NATRIUM METABISULFIT TERHADAP KARAKTERISTIK EDIBLE FILM PATI KULIT PISANG TANDUK - Hogren Leoranzen; Farida Hanum Hamzah; Rahmayuni Rahmayuni Rahmayuni (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This research was aimed to obtain the best soaking time of banana peel in sodium metabisulfite for the manufacture of edible horn banana peel starch film. This research is conducted byfour treatments andfourreplications. The treatment used was KP1 (soaking time of 24 hours), KP2 (soaking time of 26 hours), KP3 (soaking time of 28 hours) and KP4 (soaking time of 30 hours) The treatments of selected in this research was KP4 with yield of 1.9075%, thickness of 0.0829 mm, transparency of 0.05625, water vapor transmission rate of 28.0436 g/m2/hour, solubility of 22.2859%, tensile strength of 1.5287 MPa, elongation of 47.5808%, and descriptive color score of 4.5000 (not brown). Keywords:Edible film, banana horn peel, sodium metabisulfite